2015
DOI: 10.1136/gutjnl-2014-308876
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal thymic stromal lymphopoietin expression in the duodenal mucosa of patients with coeliac disease

Abstract: ObjectiveThe short isoform of thymic stromal lymphopoietin (TSLP), a cytokine constitutively expressed by epithelial cells, is crucial in preserving immune tolerance in the gut. TSLP deficiency has been implicated in sustaining intestinal damage in Crohn's disease. We explored mucosal TSLP expression and function in refractory and uncomplicated coeliac disease (CD), a T-cell-mediated enteropathy induced by gluten in genetically susceptible individuals.DesignTSLP isoforms—long and short—and receptors—TSLPR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…However, a propensity to form amphipathic helices combined with a high isoelectric point (pI) of 11.1 would support its presumed function as antimicrobial peptide6366. sfTSLP may also exhibit anti-inflammatory properties6465 and may mediate immune tolerance in the gut67.…”
Section: Discussionmentioning
confidence: 99%
“…However, a propensity to form amphipathic helices combined with a high isoelectric point (pI) of 11.1 would support its presumed function as antimicrobial peptide6366. sfTSLP may also exhibit anti-inflammatory properties6465 and may mediate immune tolerance in the gut67.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, a short isoform appears to be expressed in basal conditions, whereas a longer isoform is induced by inflammatory stimuli (12). Cleavage of human TSLP by serine proteases may also regulate TSLP protein levels or function, although it is unclear whether a similar regulatory mechanism exists in mice (13,14). TSLP genetic variants and high levels of TSLP expression have been linked to atopic diseases such as AD, asthma, allergic rhinoconjunctivitis, and EoE (15).…”
Section: Il-33mentioning
confidence: 99%
“…Biancheri et al showed a reduced mucosal TSLP expression in refractory and untreated CD, whereas Sziksz et al revealed a higher mucosal TSLP expression in patients with newly diagnosed CD [16,17]. Furthermore, previous studies showed elevated serum TSLP levels in patients with atopic dermatitis and asthma [24,18].…”
Section: Discussionmentioning
confidence: 98%
“…Biancheri et al demonstrated that TSLPR and IL-7Rα were expressed in CD mucosa, and mRNA levels of both long (lTSLP) and short TSLP (shTSLP) isoforms were reduced in CD compared with the control group [16]. Sziksz et al determined a higher mucosal expression of TSLP in patients with newly diagnosed CD than in CD patients under a gluten-free diet (GFD) and controls [17].…”
Section: Introductionmentioning
confidence: 99%